Food Hygiene Socialization: Education on Egg Quality and Management to Produce Quality Complementary Foods - Ibnu, Indra Fajarwati; Ahmad, Siti Nurhalizah (Yayasan Mestika Nusantara Satu, 2025)
Introduction: Stunting is a condition where children have a shorter body size than normal children their age and have a delay in cognitive development, resulting in physical and brain growth failure due to prolonged malnutrition. Stunting can be prevented by conducting routine pregnancy controls, providing exclusive breastfeeding for 6 months, and providing varied complementary foods (MPASI) in a timely, adequate, safe, hygienic, and correct manner. Animal protein is important to prevent stunting because it contains complete and high-quality essential amino acids. Eggs are a food of animal origin that can be used as an alternative to prevent and reduce stunting. Objective: To provide education on how to select, manage, and store eggs as food of animal origin to the community in Desa Mamminasae, Kecamatan Paleteang, Pinrang Regency. Methods: The community was educated through explanations combined with practical demonstrations of good egg selection procedures, cleaning procedures before storage, and proper egg storage positioning. Results: There was a significant increase in knowledge among participants, with an average increase in correct answers from pre-test to post-test ranging from 26.2% to 44.3% across five knowledge questions. Conclusion: The socialization program was well implemented technically and successfully improved community knowledge on egg quality management for producing quality complementary foods.